CP-ABE based users collaborative privacy protection scheme for continuous query - Lei ZHANG; Chun-guang MA; Song-tao YANG; Zeng-peng LI (Tongxin xuebao)
In location-based services (LBS),as the untrusted LBS server can be seen as an adversary,and it can utilize the attribute as background knowledge to correlate the real location of the user in the set of uncertain locations.Then the adversary can gain the location privacy when the user enjoys the snapshot and continuous query through the correlation inference attack.In order to cope with this attack,the main scheme in privacy protection is to generalize the attribute and achieve attribute anonymity.However,algorithms of this type usually assumes a trusted third party (TTP) which provides the service of similarity attribute finding and comparing,and it is unpractical in the real environment,as the TTP may become the point of attack or the bottleneck of service and it cannot be considered as the trusted one all the time.Thus,to cope with the correlation inference attack as well as the semi-trusted third party,ciphertext policy attribute based encryption (CP-ABE) and users collaboration based attribute anonymous scheme was proposed.In this scheme,the user coupled achieve location and attribute anonymity.Furthermore,this scheme could also provide security for attacks from the semi-trusted third party as well as semi-trusted collaborative users.At last,security analysis and the experiment results further verify the effectiveness of privacy protection and the efficiency of algorithm execution.